“It Is a Nomos Very Different from the Law”: on Anarchy and the Law - Marneros, Christos (Acta Universitatis Lodziensis. Folia Iuridica, 2021)
The relationship between anarchy and the law is, to say the least, an uncomfortable one. The so-called ‘classical’ anarchist position – in all its heterogeneous tendencies – is, usually, characterised by a total opposition against the law. However and despite its invaluable contribution and the ever-pertinent critique of the state of affairs, this ‘classical’ anarchist position needs to be re-examined and rearticulated if it is to pose an effective nuisance to the current (and much complex) mechanisms of domination and the oppression of dogmatism and dominance of the law. Taking into account the aforementioned challenges, in this article, I examine and develop two notions of the philosophical thought of Gilles Deleuze, namely that of the institution and that of the nomos of the nomads. In doing so, I aim to think anew the relationship between anarchy and the law and, ultimately, to point towards an ethico-political account, of what I shall call an an-archic nomos which escapes (or, at least, tries to) the dogmatism and “archist” mentality of the law.